Retail Trading in Options and the Rise of the Big Three Wholesalers - BRYZGALOVA, SVETLANA; PAVLOVA, ANNA; SIKORSKAYA, TAISIYA (Journal of Finance, 2023)
ABSTRACT We document a rapid increase in retail trading in options in the United States. Facilitated by payment for order flow (PFOF) from wholesalers executing retail orders, retail trading recently reached over 60% of total market volume. Nearly 90% of PFOF comes from three wholesalers. Exploiting new flags in transaction‐level data, we isolate wholesaler trades and build a novel measure of retail options trading. Our measure comoves with equity‐based retail activity proxies and drops significantly during U.S. brokerage platform outages and trading restrictions. Retail investors prefer cheaper, weekly options with average bid‐ask spread of 12.6%, and lose money on average.